EFFICIENCY ANALYSIS OF RICE (ORYZA SATIVA L.) FARMING BUSINESSES SIJAMBI VILLAGE, DATUK BANDAR DISTRICT TANJUNG BALAI CITY - Suci Fadilla; Nelfita Rizka S; Depari Depari; Emma Fadhilah; Abraham Ismail Pulungan (Agriprimatech, 2025)
The purpose of this study is to determine the level of efficiency in the use of production factors in rice farming, to analyze the income levels obtained by farmers, and to provide input in the form of strategies and recommendations for farmers to improve their productivity and efficiency in the future. This research employed a descriptive quantitative method with a survey approach. Data were collected directly from farmers through interviews using questionnaires, and supplemented with secondary data from relevant institutions. The respondents were rice farmers in Sijambi Village, selected based on specific criteria. The collected data were then analyzed using the Cobb-Douglas production function model to measure the extent of efficiency in the use of production factors, as well as income analysis to determine farmers’ profitability. The results show that farmers in Sijambi Village are generally quite efficient in utilizing production factors, particularly in the use of labor and fertilizers. However, inefficiencies were still found in the use of seeds and land management. The income levels obtained by farmers were relatively profitable, although there remains room for improvement to achieve more optimal results. The study recommends the adoption of modern agricultural technologies, the enhancement of farm management skills, and greater institutional support to increase rice production efficiency in the study area.